“Categorización de iniciativas estratégicas para las micro empresas comerciales en el cantón La Maná”. - Parraga Pazmiño, Gissela Jamileth (2023)
The commercial microenterprise sector is highly relevant due to its ability to generate employment and income, considering such an assertion, the present investigation was carried out whose primary objective was to categorize the strategic initiatives of commercial microenterprises in the La Maná canton to contribute to their business development. The methodology that was used maintained a mixed approach, evidencing the quantitative part in the form of information collection; while the qualitative part favored the understanding of the existing problem from the perspective of those involved. The information collected was managed through statistical procedures that optimized its presentation and understanding. The study population consisted of 3,830 owners of commercial microenterprises. The results showed that according to the ISIC International Standard Industrial Classification there are 22 categories of commercial microenterprises in the La Maná canton, of which 35% (1,322 microenterprises) correspond to the wholesale of food products, 28% (1,059 microenterprises) a Wholesale of bazaars in general, perfumery, jewelry, clothing and fur, and 6% (241 micro-enterprises) operate in activities of sale of meat products, poultry and live animals. Corrective, constructive, innovative, defensive and time-based strategic initiatives were proposed, among which are: preparing and updating an inventory of products, documenting prices, training staff, establishing business alliances, use of social networks, creating of digital catalogs, increase payment methods, establish promotions, offer free product promotions for purchases over a certain amount.